Intra-Abdominal Surgical Gauze Pseudotumor (Gossypiboma) Mimicking A Dermoid Cyst. - RehmatUllah, Al-Farah; Shuja, Samia; Gazozai, Sanaullah (International Journal of Pathology, 2018)
AbstractRetained surgical sponge or gossypiboma in the abdominal cavity following surgical operation is an avoidableiatrogenic complication, which is underreported in the literature because of medicolegal implications. Such complicationcan lead to serious morbidity and even mortality because it is not anticipated and is frequently misdiagnosed.In most instances, the retained foreign body induces a foreign body reaction which causes infection or abscessformation in the early post operative period; however pseudotumor formation rarely occurs in long termretention. Here, we describe a case of surgical gauze induced pseudotumor following an emergency hysterectomyconducted in a peripheral hospital one year ago. Clinical picture and imaging findings were suggestive ofdermoid cyst in lower abdomen. After laparotomy, gross and histological examination revealed an inflammatorypseudotumor due to gauze piece. We suggest that when an intraabdominal mass presents with a previous operativehistory, foreign body pseudotumor should be considered in the differential diagnosis